STRATEGI PENGEMBANGAN MODAL SOSIAL UNTUK PENINGKATAN KEBERDAYAAN PETANI PADI SAWAH DI KECAMATAN BUNGA RAYA KABUPATEN SIAK - Ahmad Rifai; Kausar Kausar; Mia Decnita (Indonesian Journal of Agricultural Economics, 2018)
The Government of Indonesia issued a policy to support farmers, especially rice farmers. The policy contained in the RPJM, one of them has a policy direction and the main priority target in improving the welfare of rice farmers. The policy aims to empower rice farmers. Abandoned basic capital in rice farmers empowerment is social capital. The purposes of this study are: (1) to identify the condition of rice farmers’ social capital; (2) to analyze the level of rice farmer's existence; (3) to analyze the relationship of social capital with the level of empowerment of rice farmers and (4) to formulate social capital development strategy to increase the empowerment of rice farmers. This research was conducted in Bunga Raya Subdistrict Siak Regency in two villages namely Bunga Raya and Kemuning Muda. The sampling method used was Purposive Sampling. The condition of rice farmers’ social capital in Bunga Raya District is categorized as high. The structural dimension that forms rice farmers’ social capital is of high intensity. The social capital factor analysis has 9 main indicators extracted from 21 indicators. The degree of existence of rice farmers belongs to the category of Power. The relationship between social capital and the level of empowerment of rice farmers has two correlations, namely the correlation between the structure (X1) with production (Y5) and relational (X2) with production (Y5). The strategy of social capital development for the level of empowerment of rice farmers is to build and to improve the cooperation of rice farmers in running rice farming, improving irrigation infrastructure, and provide guidance to rice farmers to recognize certified and superior rice seeds.